The safety and efficacy of adding etanercept to methotrexate or methotrexate to etanercept in moderately active rheumatoid arthritis patients previously treated with monotherapy. Issue 2 (29th August 2007) - van der Heijde, D; Burmester, G; Melo-Gomes, J; Codreanu, C; Mola, E Martin; Pedersen, R; Freundlich, B; Chang, D J
Abstract : Objective: To determine if adding etanercept (ETN) to methotrexate (MTX) or MTX to ETN for 52 weeks in rheumatoid arthritis (RA) patients with moderate disease activity provides higher efficacy. Methods: All patients (n = 227) received open-label ETN 25 mg subcutaneously twice-weekly and MTX orally up to 20 mg weekly for 52 weeks and had completed a 3-year study in which patients received MTX, ETN or combination therapy. Endpoints were based on Disease Activity Score (DAS) and European League Against Rheumatism (EULAR) responses. Results: Patients previously receiving combination therapy (Combination group; n = 96) had a lower disease activity at baseline. The mean DAS for those previously receiving MTX (ETN-added group; n = 55) and previously receiving ETN (MTX-added group; n = 76) were in the moderate disease activity range at baseline; Combination patients had a low disease activity. The greatest increase in DAS remission rates from baseline to week 52 was in the ETN-added group (23.6% to 41.8%, p<0.01), although Combination (37.6% to 50.0%, p<0.01) and MTX-added (26.7% to 36.8%, p = NS) also demonstrated improvements. DAS low disease activity and EULAR responses showed similar results. No new safety issues were identified. Conclusion: RA patients who were partial responders to long-term MTX or etanercept monotherapy obtained a higher efficacy with combination therapy. Responses achieved by patients with combination therapy after 3 years in the previous study were sustained or improved during the fourth year of treatment. This trial supports the higher therapeutic effect of combination treatment with etanercept and MTX in RA patients with moderate disease activity despite monotherapy with one of the two agents.